Thrombocytopenia and platelet hypoaggregation induced by Bothrops asper snake venom Toxins involved and their contribution to metalloproteinase-induced pulmonary hemorrhage - Rucavado, Alexandra; Soto, Mónica; Escalante, Teresa; Loría, Gilbert D.; Arni, Raghuvir [UNESP]; Gutiérrez, José María (Schattauer Gmbh-verlag Medizin Naturwissenschaften, 2005)
Thrombocytopenia and platelet dysfunction occur in patients bitten by Bothrops sp snakes in Latin America. An experimental model was developed in mice to study the effects of B. asper venom in platelet numbers and function. Intravenous administration of this venom induces rapid and prominent thrombocytopenia and ex vivo platelet hypoaggregation. The drop in platelet numbers was primarily due to aspercetin, a protein of the C-type lectin family which induces von Willebrand factor-mediated platelet aggregation/agglutination. In addition, the effect of class P-III hemorrhagic metalloproteinases on the microvessel wall also contributes to thrombocytopenia since jararhagin, a P-III metalloproteinase, reduced platelet counts. Hypoaggregation was associated with the action of procoagulant and defibrin(ogen)ating proteinases jararacussin-1 (a thrombin-like serine proteinase) and basparin A (a prothrombin activating metalloproteinase). At the doses which induced hypoaggregation, these enzymes caused defibrin(ogen)ation, increments in fibrin(ogen) degradation products and D-dimer and prolongation of the bleeding time. Incubation of B. asper venom with batimastat and α 2-macroglobulin abrogated the hypoaggregating activity, confirming the role of venom proteinases in this effect. Neither aspercetin nor the defibrin(ogen)ating and hypoaggregating components induced hemorrhage upon intravenous injection. However, aspercetin, but not the thrombin-like or the prothrombin-activating proteinases, potentiated the hemorrhagic activity of two hemorrhagic metalloproteinases in the lungs. © 2005 Schattauer GmbH, Stuttgart.
Keywords: Coagulopathy; Defibrin(ogen)ation; Hypoaggregation; Snake venom; Thrombocytopenia; Alpha 2 macroglobulin; Batimastat; D dimer; Fibrinogen degradation product; Lectin; Metalloproteinase; Procoagulant; Serine proteinase; Snake venom; Von Willebrand factor; Animal experiment; Animal model; Bleeding time; Blood clotting parameters; Controlled study; Ex vivo study; Mouse; Nonhuman; Priority journal; Snake; Thrombocyte agglutination; Thrombocyte aggregation; Thrombocyte count; Thrombocyte function; Thrombocytopenia; Alpha-Macroglobulins; Animals; Bleeding Time; Blood Platelets; Bothrops; Dose-Response Relationship, Drug; Fibrin Fibrinogen Degradation Products; Hemorrhage; Humans; Lung; Metalloendopeptidases; Metalloproteases; Mice; Platelet Aggregation; Snake Venoms; Time Factors; von Willebrand Factor